Adverse Childhood Experiences as a significant predictor of worsened well-being among Polish medical and dental students - Paulina Drożak; Katarzyna Augustowska; Łukasz Bryliński; Agata Bura; Martyna Drożak; Piotr Duda; Ewa Rudnicka-Drożak (Kazimierz Wielki University, 2021)
Introduction and purpose. Adverse Childhood Experiences (ACEs) are a major public health problem. The aim of the study was to investigate the prevalence of Adverse Childhood Experiences among medical and dental students in Poland and to examine a relationship between ACEs and chosen factors associated with well-being of the students. Material and method. The research tool consisted of the Adverse Childhood Experiences standardized questionnaire and authors' questions. 934 medical students and 228 dental students took part in the study (a total of 1162 participants). The respondents came from 18 Polish universities. Results. 57.40% of the students experienced at least 1 childhood adversity, 8.43% of them were affected by 4 or more ACEs. The most common adverse childhood experiences were: emotional neglect (23.06%), emotional abuse (22.98%) and mental illness or a suicide attempt in a household member (21.86%). On average, women experienced more childhood adversities than men. An overall graded relationship was found between ACEs and: frequent feelings of loneliness, low self-assessment of academic performance, problems with maintaining stable body weight, reaching for alcohol in order to de-stress and being non-religious. Conclusions. Adverse Childhood Experiences are common among Polish medical and dental students and are linked with multiple aspects of worsened well-being of the students. The study emphasizes a need to create strategies that aim to educate on Adverse Childhood Experiences in order to prevent them and help those who are affected by them.